Are metal-free pristine carbon nanotubes electrocatalytically active? - Cheng, Yi; Zhang, J.; Jiang, San Ping (Royal Society of Chemistry, 2015)
Metal-free (i.e., residual metallic impurities-blocked) carbon nanotubes (CNTs) do show electrocatalytic activity for H2 evolution, O2 evolution and O2 reduction reactions (HER, OER & ORR) in alkaline solutions, but their activities strongly depend on the number of walls or inner tubes with a maximum for CNTs with 2–3 walls.